The staircase in the Burgtheater and the Town Hall in Vienna - Hielscher, Kurt, 1881-1948 (photographer):::Creator:::::::::::: (2020)
Photogravures with images of the staircase in the Burgtheater and the Town Hall (Rathaus) in Vienna